Serum nitrite and nitrate levels, NOx, can predict cardiovascular mortality in the elderly in a 3‐year follow‐up study. (18th August 2016) - Gumanova, Nadezhda G.; Deev, Alexander D.; Zhang, Wei; Kots, Alexander Y.; Shalnova, Svetlana A.
Abstract: Nitric oxide (NO) is an important functional regulator that contributes to progression of various cardiovascular diseases. We studied associations between nitric oxide metabolites, nitrite and nitrate (NOx), and cardiovascular mortality in a prospective 3‐year follow‐up cohort study in 1, 869 elderly patients aged over 55 years. The Cox proportional hazard regression model was adjusted for multiple factors including sex, age, risk corresponding to preexisting cardiovascular conditions, and serum inflammatory markers (C‐reactive protein, interleukin‐6, fibrinogen, and leucocytes count). During the follow‐up period, there were a total of 348 deaths including 216 deaths unrelated to cardiovascular events and 132 cardiovascular deaths. Cox regression adjusted for factors related to cardiovascular disease risks and inflammatory markers showed a significant association between high levels of serum nitric oxide metabolites, NO x, and increased cardiovascular mortality (hazard ratio 2.21; 95% confidence interval 1.13–4.31) but there was no association with non‐cardiovascular mortality. Analysis of adjusted hazard ratios demonstrates that association of serum nitric oxide metabolites with cardiovascular mortality was independent of levels of inflammatory markers. Thus, elevated concentrations of serum nitric oxide metabolites are a predictor of cardiovascular mortality and may be used as an integral marker of cardiovascular death. © 2016 BioFactors, 43(1):82–89, 2017